g+47=-65

Simple and best practice solution for g+47=-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+47=-65 equation:


Simplifying
g + 47 = -65

Reorder the terms:
47 + g = -65

Solving
47 + g = -65

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-47' to each side of the equation.
47 + -47 + g = -65 + -47

Combine like terms: 47 + -47 = 0
0 + g = -65 + -47
g = -65 + -47

Combine like terms: -65 + -47 = -112
g = -112

Simplifying
g = -112

See similar equations:

| 4(6m+5)=-172 | | y-126=27 | | -4-4=11x+2x | | -81=-5-4(1-3a) | | -4x-8=6x+3 | | 2-5x+4= | | 3x-1+4x-9+9x=15x+2 | | x+22=27 | | 29y=28y-14 | | f(0.4)=0.6 | | 7+x=32 | | 128=-5(5+5n)+3 | | -3(-2-5c)= | | 3(6p+1)=111 | | m+6m= | | 16+x=-1 | | 6d+9+3d= | | 0.2=-Log(X) | | 70x^2-67x+72=0 | | 3m+4+5m=-6 | | 3m+18=4m+10 | | y-30,y=10 | | 3(x+iy)-i(x-iy)=16 | | -9(3x-4)=24 | | 8w-6(-3w-5)= | | -134=-2(8x-2)-7x | | x-13,x=20 | | 8(x-7)=8 | | (14x+9)(5x-8)=0 | | 180=5(8-4x) | | 6z-8=7x-1 | | (-n+1)(-8n-1)= |

Equations solver categories